2020
DOI: 10.1101/2020.12.01.406777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Competition between parallel sensorimotor learning systems

Abstract: Sensorimotor adaptation benefits from learning in two parallel systems: one that has access to explicit knowledge, and another that relies on implicit, unconscious correction. However, it is unclear how these systems interact: does enhancing one system's contributions, for example through instruction, impair the other, or do they learn independently? Here we illustrate that certain contexts can lead to competition between implicit and explicit learning. In some cases, each system is responsive to a task-relate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 83 publications
(289 reference statements)
8
37
1
Order By: Relevance
“…In addition, we confirmed a previous finding of incomplete learning of the implicit process as depicted in all groups of the task-irrelevant error-clamp condition. This lower asymptote of the implicit component is consistent with previous reports (Kim et al, 2018), suggesting that this phenomenon probably reflects a balance between learning from errors and forgetting of the adaptive state from one trial to the next (Shmuelof et al, 2012;van der Kooij et al, 2015) Recent reports suggested that the implicit process could also be driven, at least in part, by performance errors and responds to strategic explicit processes (Albert et al, 2020). This is in line with previous studies that showed that strategy use interferes with the build-up of implicit adaptation (Benson et al, 2011;Jakobson & Goodale, 1989), as strategy use would decrease the performance errors that could drive implicit adaptation.…”
Section: Follow-through Movements Allow Separation Of Opposing Memories Through Explicit and Implicit Processessupporting
confidence: 89%
“…In addition, we confirmed a previous finding of incomplete learning of the implicit process as depicted in all groups of the task-irrelevant error-clamp condition. This lower asymptote of the implicit component is consistent with previous reports (Kim et al, 2018), suggesting that this phenomenon probably reflects a balance between learning from errors and forgetting of the adaptive state from one trial to the next (Shmuelof et al, 2012;van der Kooij et al, 2015) Recent reports suggested that the implicit process could also be driven, at least in part, by performance errors and responds to strategic explicit processes (Albert et al, 2020). This is in line with previous studies that showed that strategy use interferes with the build-up of implicit adaptation (Benson et al, 2011;Jakobson & Goodale, 1989), as strategy use would decrease the performance errors that could drive implicit adaptation.…”
Section: Follow-through Movements Allow Separation Of Opposing Memories Through Explicit and Implicit Processessupporting
confidence: 89%
“…However, we did observe that reaction time (Fig. S1A) appeared elevated after passive training in the experimental groups, which is known to commonly accompany cognitive operations (Fernandez-Ruiz et al, 2011; Sakamoto and Kondo, 2012; Anguera et al, 2010; Georgopoulos and Massey, 1987; McDougle et al, 2019; Albert et al, 2020).…”
Section: Discussionmentioning
confidence: 73%
“…When people adapt to two similar perturbations consecutively, re-adaptation evokes a hallmark of sensorimotor adaptation called savings: more rapid learning during the second exposure to a perturbation (Smith et al, 2006; Zarahn et al, 2008; Leow et al, 2013; Haith et al, 2015; Day et al, 2018; Coltman et al, 2020; Yin & Wei, 2020). These changes in learning are thought to be mediated by error sensitivity (Gonzalez-Castro & Hadjiosif, 2014; Herzfeld et al, 2014; Coltman et al, 2020), whereby the trial-by-trial experience of consistent errors makes the brain more sensitive to those errors in the future (Herzfeld et al, 2014; Leow et al, 2016; Albert et al, 2020). Do these changes in the brain’s learning systems require errors to be actively experienced, or can learning be improved by passive experiences as well?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations